Special Issue: 2021 Research Data Access and Preservation Summit - Caitlin Bakker; Heather L. Coates; Sara Mannheimer (Journal of eScience Librarianship, 2021)
The Journal of eScience Librarianship has partnered with the Research Data Access and Preservation (RDAP) Association for a fourth year to publish selected conference proceedings.